Organ-On-A-Chip Models of the Blood–Brain Barrier: Recent Advances and Future Prospects - Kawakita, Satoru; Mandal, Kalpana; Mou, Lei; Mecwan, Marvin Magan; Zhu, Yangzhi; Li, Shaopei; Sharma, Saurabh; Hernandez, Ana Lopez; Nguyen, Huu Tuan; Maity, Surjendu; de Barros, Natan Roberto; Nakayama, Aya; et al. (Wiley, 2022)
The human brain and central nervous system (CNS) present unique challenges in drug development for neurological diseases. One major obstacle is the blood–brain barrier (BBB), which hampers the effective delivery of therapeutic molecules into the brain while protecting it from blood-born neurotoxic substances and maintaining CNS homeostasis. For BBB research, traditional in vitro models rely upon Petri dishes or Transwell systems. However, these static models lack essential microenvironmental factors such as shear stress and proper cell–cell interactions. To this end, organ-on-a-chip (OoC) technology has emerged as a new in vitro modeling approach to better recapitulate the highly dynamic in vivo human brain microenvironment so-called the neural vascular unit (NVU). Such BBB-on-a-chip models have made substantial progress over the last decade, and concurrently there has been increasing interest in modeling various neurological diseases such as Alzheimer's disease and Parkinson's disease using OoC technology. In addition, with recent advances in other scientific technologies, several new opportunities to improve the BBB-on-a-chip platform via multidisciplinary approaches are available. In this review, an overview of the NVU and OoC technology is provided, recent progress and applications of BBB-on-a-chip for personalized medicine and drug discovery are discussed, and current challenges and future directions are delineated.
Keywords: blood–brain barriers; disease modeling; drug discovery; organ-on-a-chips; personalized medicine